A NEWLY DEVELOPED PHANTOM FOR PHYSICAL QUALITY ASSURANCE OF DENTAL CONE-BEAM COMPUTED TOMOGRAPHY. Issue 3 (25th July 2018) - Bamba, Junko; Ishida, Hideki; Araki, Kazuyuki
Abstract: Two phantoms for a performance evaluation of cone-beam computed tomography (CBCT) were developed and their efficiency was tested. The first phantom, for low-contrast resolution, consisted of an acrylic circular plate with three 0.5–1.0 mm diameter rods. These rods enable the user to visually evaluate the limit of observation. The second phantom, for geometric distortion, especially focused on the z -axis and consisted of two tabular acryl plates crossed perpendicularly with 1.0 mm-wide grooves in a grating form every 10.0 mm. The distances between the grooves on the axial and coronal images were evaluated. Five CBCT modalities were assessed using these phantoms. The contrast resolutions differed for each apparatus and set of exposure parameters. In terms of geometric distortion, some distortion was observed at the periphery of the field of view for both the axial and z -axis planes. These results suggest that our new phantoms can be used to evaluate CBCT.